Case report Chronic mucocutaneous candidiasis with endocrinopathy – case report - Lesiak, Aleksandra; Erkiert-Polguj, Anna; Dziankowska-Bartkowiak, Bożena; Sysa-Jędrzejowska, Anna; Narbutt, Joanna (Archives of Medical Science, 2010)
Chronic mucocutaneous candidiasis (CMC) is characterized by Candida infection of the mucous membrane, scalp, skin and nails. We present a case of a 42-year-old man who was treated twice in the Dermatological Department. He was admitted the first time as a 7-year-old boy because of skin and mucosal lesions and then the diagnosis of granuloma candidamyceticum was established. Thirty-one years later he was admitted again with a history of facial skin lesions and blepharitis. For a couple of years he had suffered from diabetes and hypothyroidism. The diagnosis of CMC with endocrinopathy was established in our patient.